A complex CLCN1 variant associated with hereditary myotonia in a mixed-breed dog - Chimenes, Natielly D. D.; Caramalac, Silvana M. M.; Caramalac, Simone M. M.; Fernandes, Thiago D. D.; Basso, Roberta M. M. [UNESP]; Cerri, Fabricio M. [UNESP]; Oliveira-Filho, Jose P. [UNESP]; Borges, Alexandre S. S. [UNESP]; Palumbo, Mariana I. P. (Sage Publications Inc, 2023)
Hereditary myotonia (HM) is characterized by delayed muscle relaxation after contraction as a result of a mutation in the CLCN1 gene. We describe here a complex CLCN1 variant in a mixed-breed dog with clinical and electromyographic signs of HM. Blood samples from the myotonic dog, as well as from his male littermate and parents, were analyzed via amplification of the 23 exons encoding CLCN1. After sequencing the CLCN1 gene, a complex variant was found in exon 6 c.[705T>G; 708del; 712_732del], resulting in a premature stop codon in exon 7 and a protein that was 717 amino acids shorter than the normal CLC protein. The myotonic dog was identified as homozygous recessive for the complex CLCN1 variant; its parents were heterozygous, and its male littermate was homozygous wild-type. Knowledge of the CLCN1 mutations responsible for the development of hereditary myotonia allows greater clarification of this condition.
Keywords: chloride channel; dogs; electromyography; genetic analyses; hereditary; myopathy